Small cinemas in global markets : genres, identities, narratives - Giukin, Lenuta; Falkowska, Janina; Desser, David (Lexington, 2015)
This volume focuses on debates and changes in small cinema industries, analyzing the impact of expansion and diversification of the cinematic product at local, regional, and global levels. Contributors use Western theoretical perspectives with a professional (mostly native) knowledge of the language, cultural realities, and film industry practices.